Brackish water irrigation on the characteristics of carbon, nitrogen and phosphorus nutrients in the soil nearby crop roots - Li, Yun (Emirates Journal of Food and Agriculture, 2018)
To study the effect of brackish water on carbon, nitrogen and phosphorus in the soil nearby root zone of crops. By analyzing the influence of different levels of salt and fresh water combination irrigation on organic carbon, nitrogen and phosphorus migration rule in the soil, and the dynamic change rule in different sections to investigate the spatial distribution of each index at the end of the experiment. According to the soil properties and root distribution of Zizyphusjujuba, brackish water drip irrigation quota, irrigation water salinity and fertilization measures of root zone, different gradient levels of combined irrigation experiments were set up. The experiment with fresh water was used as control to establish orthogonal test scheme. The content of carbon, nitrogen and phosphorus in soil nearby crop roots was measured, and the measurement of carbon, nitrogen and phosphorus in the soil nearby crop roots was utilized to analyze the effect of brackish water irrigation on the soil nearby crop roots. With the increase of brackish water amount for irrigation, nitrate and alkali nitrogen content in the soil nearby roots was significantly decreased, and the reduction trend is going up after a significant amount of brackish water for irrigation is added. While phosphorus content decreased at different levels after brackish water amount for irrigation was increased, but the decrease is not significant. Brackish water irrigation with appropriate amount of salt can improve the effective utilization rate of carbon and nitrogen and phosphorus in soil, and result in higher yield for crops. The fruit set is the highest under brackish water irrigation with 3 g/L salt.